IMBPiracy's Twitter Sentiment Analysis for Indonesia with Nvivo 12 Plus - Chalid Darmawan; Rudiyanto Rudiyanto; Bayu Asih Yulianto; Pujo Widodo; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
The rapid advancement of technology is matched by the rapid dissemination of information via social media, including information related to piracy. On the other hand, in maritime sociology conflicts, the presence of social media can polarize the international community, damage peace movements, promote violent agendas, and spread false and inaccurate information. Twitter is one of the social media platforms whose data is still open for processing. Writing this article aims to find out positive and negative sentiments about piracy news in Indonesia from Twitter IMBPiracy using the Nvivo 12 plus application. The method used is descriptive qualitative to describe the results of IMBPiracy's Twitter sentiment analysis with the Nvivo 12 Plus application. The data was taken from IMBPiracy's official Twitter from 2010 to 2022 using the Ncapture application. From the data collected, it is then analyzed to find out the country of origin and the number of negative and positive tweets. In this study, the results were found, namely IMBPiracy's tweets were dominated by France, which contributed 47 tweets. Meanwhile, an analysis of IMBPiracy's tweets about piracy in Indonesia shows mostly negative sentiment. Of course, these negative tweets can hurt the identity of the Indonesian nation as a formidable maritime nation.